CHARACTERISTIZATION OF WATER ABSORPTION BEHAVIOUR, SEM, AND EDS ON COMMERCIAL DENTAL COMPOSITES - Imran, Al Ichlas (Barometer, 2022)
Dental material is a composite composed of a hydrophilic matrix and filler as a reinforcement. Liquid enters the mouth and passes through the dental material by diffusion and damage the material, thereby interfering with the teeth's ability to chew food. The purpose of this study is to study the fluid absorption behavior of three types of dental composites and to determine the surface structure and its composition. The commercial filling composites used were Solare®X-A3, FiltekTMZ350XT Flow-A3 and Grandio®Flow-A3. The immersion medium was artificial saliva pH 7 and Coca-Cola® pH 3.45. Specimens were molded into an acrylic and hardened using light curing for 1 minute. The fluid absorption behavior was carried out by immersing the specimen in artificial saliva and Coca-Cola® media. Specimen weight was recorded periodically every 1-4 days for 38 days. Observation of the surface structure used SEM and chemical composition analysis with EDS for Filtek. The results showed that the fluid absorption behavior of all dental composites from 4 to 38 day increased, where the composites immersed in Coca-Cola® gained greater weight than artificial saliva. For the surface structure of the Filtek, the condition before immersion shows the wide contact surface between the filler and the matrix, and the condition after immersion shows the presence of empty space and swelling of the matrix. The results of the chemical composition analysis, before immersion showed that Filtek was composed of elements C, O, Si, Zr and Yb, where after immersion showed the element Yb had dissolved with Coca-Cola® liquid.